Reproducibility of quantitative greyscale and shear wave ultrasound measures of the supraspinatus tendon in individuals without shoulder pain or pathology - Hogaboom, Nathan S; Vyas, Krina; Barrance, Peter (Journal of biomechanics, 2025)
Ultrasound and shear wave elastography (SWE) are powerful imaging modalities to assess biomarkers of tendon health. These include markers of collagen content and fiber alignment (echogenicity) and tissue stiffness (elasticity). Changes in these metrics could be useful when investigating tissue perturbations after intervention or activity. In the few studies that have investigated reliability of these measures in the supraspinatus tendon, technological limitations of the ultrasound devices imposed shear wave speed ceiling effects and likely biased their findings. The purpose of this study was to determine reliability statistics (intraclass correlation coefficients [ICCs], standard errors of measurement [SEMs], minimal detectable changes [MDCs]) of supraspinatus tendon elasticity and echogenicity among a cohort of ten young, pain-free individuals. Two investigators collected greyscale and SWE images of their supraspinatus tendons in longitudinal view. Each participant was imaged twice, separated by approximately one hour. Five participants returned four months later, and the imaging protocol was repeated. ICCs were “excellent” for echogenicity intra- and inter-rater reliabilities (≥91) at both time points. Elasticity was more varied – inter-rater ICCs ranged from “fair” (0.61) to “good” (0.89), whereas intra-rater ICCs were “good” to “excellent” across both timepoints (0.86–0.95). Large SEMs and wide ranges of agreement between raters suggest that while these measures are reliable, a single investigator should collect all images within the same subject to optimize measurement precision. Reported SEMs and MDCs can aid during interpretation of findings in future studies.